(3x-5)(3x+4)=

Simple and best practice solution for (3x-5)(3x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-5)(3x+4)= equation:


Simplifying
(3x + -5)(3x + 4) = 0

Reorder the terms:
(-5 + 3x)(3x + 4) = 0

Reorder the terms:
(-5 + 3x)(4 + 3x) = 0

Multiply (-5 + 3x) * (4 + 3x)
(-5(4 + 3x) + 3x * (4 + 3x)) = 0
((4 * -5 + 3x * -5) + 3x * (4 + 3x)) = 0
((-20 + -15x) + 3x * (4 + 3x)) = 0
(-20 + -15x + (4 * 3x + 3x * 3x)) = 0
(-20 + -15x + (12x + 9x2)) = 0

Combine like terms: -15x + 12x = -3x
(-20 + -3x + 9x2) = 0

Solving
-20 + -3x + 9x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-4 + -3x)(5 + -3x) = 0

Subproblem 1

Set the factor '(-4 + -3x)' equal to zero and attempt to solve: Simplifying -4 + -3x = 0 Solving -4 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -3x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -3x = 0 + 4 -3x = 0 + 4 Combine like terms: 0 + 4 = 4 -3x = 4 Divide each side by '-3'. x = -1.333333333 Simplifying x = -1.333333333

Subproblem 2

Set the factor '(5 + -3x)' equal to zero and attempt to solve: Simplifying 5 + -3x = 0 Solving 5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 0 + -5 -3x = 0 + -5 Combine like terms: 0 + -5 = -5 -3x = -5 Divide each side by '-3'. x = 1.666666667 Simplifying x = 1.666666667

Solution

x = {-1.333333333, 1.666666667}

See similar equations:

| 5+22a=2+.45 | | 17+5n/4= | | 2x-4=2x+3 | | 1/3(x-8)=10 | | x/4-5/3=1/12 | | x^2-9x-5=-5x | | 5(2d+4)=36 | | 8y+4(8+y)=3(y-3)+10y | | 5x+98=2 | | -5b=7b | | (8x+6)/12=(3x/5)+2 | | 6/5x-3/5x=-7/3-4/3 | | 1/3x+2/4x+x+18+x+60+2x=540 | | -4x-12=16 | | -140/8-20/8=x | | 2x-(6x-2)=1 | | r=r+5 | | l=7(3.14)r | | 3g+11-5g=17 | | 11x-8+4x+x+7= | | 3x^2+2x-3x^2+9= | | 2(x-2)+3x=-3(2x+1) | | .25(16+4t)-.5(10+2t)= | | -7x=4x+62 | | 2x^2-x^4-1=0 | | 7x=4x+62 | | x(5x-9)=(5x+9)(x-3) | | (-76)+(-37)-38+(-60)= | | 2(2h+1)+3(4h+7)= | | -2/3+(-7/2) | | -3x+7y=5 | | (4-9)(13-16)+5= |

Equations solver categories